Management of central nervous system teratoma. Issue 1 (January 2015) - Zygourakis, Corinna C.; Davis, Jessica L.; Kaur, Gurvinder; Ames, Christopher P.; Gupta, Nalin; Auguste, Kurtis I.; Parsa, Andrew T.
Abstract Central nervous system (CNS) teratomas are very rare neoplasms that contain tissues derived from all three germ cell layers (endoderm, mesoderm, and ectoderm). Patients with teratomas usually have a good prognosis. Given the paucity of cases in the literature, we present a retrospective review of 15 CNS teratomas treated over a 25 year period at the University of California, San Francisco. We describe the presentation, location, treatment, and adjuvant therapy for these patients, and highlight three unique cases that emphasize the diverse presentation and treatment of these rare tumors.